CONSTRUCTION OF VASCULAR GRAFT BY 3D PRINTING USING BACTERIAL CELLULOSE FORMULATION AS BIOINK - Cesur, Nevra Pelin; Lacin, Nelisa Turkoglu (EDITURA ACAD ROMANE, 2022)
Currently, there is a considerable clinical demand for biocompatible and robust tissue-engineered artificial vascular graft materials. The vascular application requiring adequate mechanical strength and biocompatibility still lags at some critical points. Bacterial cellulose (BC) is well known for its use as a biomaterial in various fields due to its high biocompatibility. The most critical issue preventing the wide use of BC for 3D biomaterial printing is its insolubility in water and organic solvents. Because of this feature, the use of BC as bioink is limited. In this study, optimizing the solubility of BC with zinc sulphate, and the application of the obtained bioink with a 3D printing technique to create a model vascular graft, as well as examining it in terms of mechanical strength, were carried out for the first time in the literature. The chemical characterization of the obtained vascular graft was performed by FTIR, RAMAN and SEM analyses. The thermal behavior was analyzed by TG analysis (showing mass losses of 22.72% at 361 degrees C and 52.4% at 421 degrees C). The surface area was measured as 8.290 m(2)/g. The water retention capacity (WRC) was examined throughout 48 hours (after 1 h - 5%, 24 h - 9%, and 48 h - 9%). The elasticity modulus of the sample was 172.083 N/mm(2) and the elongation break was 87.591%. The cytotoxicity analysis results revealed that cell viability reached 75.84% on the only resin-containing 3D-printed aorta, while it was 100% on the BC/zinc sulfate-resin composite 3D-printed aorta. The morphology of the human umbilical vein endothelial cells (HUVECs) was observed after 24, 52 and 72 h. Cell adhesion to the BC-based composite 3D printed vascular graft was determined as 89.02% after 24 h, 92.01% after 52 h, 100% after 72 h, while it reached much lower values for the only resin-containing 3D vascular graft - of 55.02% after 24 h, 56% after 48 h, and 58.04% after 72 h. Additionally, the rheological analysis indicated that the yield stress of the BC-based bioink increased with the BC content up to 20 Pa.
Keywords: 3D printing; patient-specific vascular graft; tissue engineering; NANOFIBER DENSITY; IN-SITU; CELL; TISSUE; SCAFFOLDS; POROSITY; Materials Science